Purinergic Activation of Store-Operated Calcium Entry (SOCE) Regulates Cell Migration in Metastatic Ovarian Cancer Cells - Esperanza Mata-Martínez; Adriana Gonzalez-Gallardo; Mauricio Díaz-Muñoz; Francisco G. Vázquez-Cuevas (MDPI AG, 2023)
Store-operated calcium entry (SOCE) is an important process in calcium signaling. Its role in physiological and pathological events is well recognized. However, in cancerous systems, the importance of SOCE in relation to the degree of cancer aggressiveness, as well as its regulation by ligands such as purinergic molecules, are not well documented. This study aimed to characterize a differential effect of the P2Y2 receptor (promoted by UTP of 10 µM and inhibited by ARC118925XX of 1 µM) on intracellular calcium response between metastatic (SKOV-3) and non-metastatic (CAOV-3) ovarian cell lines in conditions of normal (1.5 mM) and zero extracellular calcium concentration. The sustained calcium influx observed exclusively in SKOV-3 cells was associated with the presence of SOCE (promoted by thapsigargin (74.81 ± 0.94 ΔF) and sensitive to 2-APB (20.60 ± 0.85 ΔF)), whereas its absence in CAOV-3 cells (26.2 ± 6.1 ΔF) was correlated with a low expression of ORAI1. The relevance of SOCE in metastatic SKOV-3 cells was further corroborated when 2-APB significantly inhibited (40.4 ± 2.8% of covered area) UTP-induced cell migration (54.6 ± 3.7% of covered area). In conclusion, our data suggest that SOCE activation elicited by the P2Y2 receptor is involved in the aggressiveness of ovarian cancer cells.